2021
DOI: 10.1186/s13052-021-01109-1
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden and quality of life in children with sickle cell disease in Italy: time to be considered a priority

Abstract: The objective of the present article is to highlight the need for attention to Quality of Life of patients with Sickle Cell Disease living in Italy. The transformation of sickle cell disease from a severe life-threatening disease of childhood into a chronic, lifelong condition due to the significant improvements in care and treatment options, imposes increasing new challenges to health care providers and patients. Patients now face physical, psychosocial and emotional challenges throughout their lives. They ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1,3 Consequently, enabling the best possible (health-related) quality of life is a central aspect of patient care, which is increasingly being pursued in current treatment strategies. 4,5 Having (biological) children has been reported as a relevant life goal in a small cohort of patients with SCD. 6 The underlying congenital anemia itself, as well as applied treatments such as regular blood transfusions (RBT) and/or hydroxyurea (HU), have been associated with an increased risk of fertility impairment in both men and women with hemoglobinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Consequently, enabling the best possible (health-related) quality of life is a central aspect of patient care, which is increasingly being pursued in current treatment strategies. 4,5 Having (biological) children has been reported as a relevant life goal in a small cohort of patients with SCD. 6 The underlying congenital anemia itself, as well as applied treatments such as regular blood transfusions (RBT) and/or hydroxyurea (HU), have been associated with an increased risk of fertility impairment in both men and women with hemoglobinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…A chronic disease affects all parts of a patient's life, not just the physical, but also the social and emotional, educational, and occupational aspects [6] . physical wellness defines as a consist of recognition the need for physical activities, healthy diet and sleeping as well as prevention illness and injury or managing chronic health problems [7] .…”
Section: Introductionmentioning
confidence: 99%
“…It is most prevalent in sub Saharan Africa with an estimated 12 -15 million cases (Henrici et al, 2021). Children with sickle cell anemia have vaso-occlusion, chronic hemolytic anemia and vasculopathy that cause both acute and chronic complications, which have a profound impact on the quality of life (Colombatti et al, 2021). Findings of many studies on children with SCA revealed that health related quality of life, in terms of pain, suffering and emotional functioning, significantly declined with increasing age of the child (CDC, 2020).…”
Section: Introductionmentioning
confidence: 99%